Five novel bifidobacterial species isolated from faeces of primates in two Czech zoos: Bifidobacterium erythrocebi sp. nov., Bifidobacterium moraviense sp. nov., Bifidobacterium oedipodis sp. nov., Bifidobacterium olomucense sp. nov. and Bifidobacterium panos sp. nov - Neuzil-Bunesova, Vera; Lugli, Gabriele Andrea; Modrackova, Nikol; Vlkova, Eva; Bolechova, Petra; Burtscher, Johanna; Longhi, Giulia; Mancabelli, Leonardo; Killer, Jiri; Domig, Konrad; Ventura, Marco (International journal of systematic and evolutionary microbiology, 2021)
Five Bifidobacterium strains, VB23T, VB24T, VB25T, VB26T and VB31T, were isolated from chimpanzee (Pan troglodytes), cotton-top tamarin (Saguinus oedipus), Goeldi's marmoset (Callimico goeldii), moustached tamarin (Saguinus mystax) and patas monkey (Erythrocebus patas), respectively, which were kept in two Czech zoos. These strains were isolated from faecal samples and were Gram-positive, non-motile, non-sporulating, anaerobic and fructose-6-phosphate phosphoketolase-positive. Phylogenetic analyses based on 16S rRNA revealed close relatedness between VB23T and Bifidobacterium angulatum LMG 11039T (96.0 %), VB24T and Bifidobacterium pullorum subsp. pullorum DSM 20433T (96.1 %), VB25T and Bifidobacterium goeldii LMG 30939T (96.5 %), VB26T and Bifidobacterium imperatoris LMG 30297T (98.1 %), and VB31T and B. angulatum LMG 11039T (99.40 %). Internal transcribed spacer profiling revealed that VB23T, VB24T, VB25T, VB26T and VB31T had highest similarity to Bifidobacterium breve LMG 13208T (77.2 %), Bifidobacterium longum subsp. infantis ATCC 15697T (85.8 %), Bifidobacterium biavatii DSM 23969T (76.9 %), B. breve LMG 13208T (81.2 %) and B. angulatum LMG 11039T (88.2 %), respectively. Average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) analyses with their closest neighbours supported the independent phylogenetic positions of the strains with values between 86.3 and 94.3 % for ANI and 25.8 and 54.9 % for dDDH. These genomic and phylogenetic analyses suggested that the evaluated strains were novel Bifidobacterium species named Bifidobacterium erythrocebi sp. nov. (VB31T=DSM 109960T=CCUG 73843T), Bifidobacterium moraviense sp. nov. (VB25T=DSM 109958T=CCUG 73842T), Bifidobacterium oedipodis sp. nov. (VB24T=DSM 109957T=CCUG 73932T), Bifidobacterium olomucense sp. nov. (VB26T=DSM 109959T=CCUG 73845T) and Bifidobacterium panos sp. nov. (VB23T=DSM 109963T=CCUG 73840T).
Keywords: zastoupení bazí; taxonomy; Feces; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; monkeys; Česká republika; mastné kyseliny; Phylogeny; Sequence Analysis, DNA; sekvenční analýza DNA; Nucleic Acid Hybridization; Animals, Zoo; Fatty Acids; hybridizace nukleových kyselin; Czech Republic; DNA, Bacterial; captivity; DNA bakterií; Animals; zvířata v ZOO; phylogenomics; FAMEs; zvířata; Base Composition; Bifidobacterium; Primates; RNA ribozomální 16S; Bacterial Typing Techniques; primáti; feces